Asuhan Keperawatan pada Ny. W Keluarga Tn. J dengan Gangguan Sistem Muskuloskeletal : Rheumatoid Arthritis di Desa Kalibuntu RT 04 RW 04 Kecamatan Losari Kabupaten Brebes - Nabiel Azkiya; Ahmad Zakiudin; Anna Maulina Lestari (NAJ Nursing Applied Journal, 2024)
Rheumatism is a disease in which the body attacks its own joints. As a result, the joints become swollen, painful and mayy change shape. This disease not only attacks the joints, but also important organ such as the hearth and lungs. The purpose of this paper is to provide nursing care to the family of Mr. M who has members with rheumatism. Mr.M’s family who has a member with rheumatism. The author will conduct assesment, diagnosis, implementation and evaluation of the health problems faced by the family. The methods used are interviews, observation and dokumentation. The results of this writing are expected to be a new innovation in providing effective family nursing care for people with rheumatism in the community.